A continuum mechanical modelling of mullins effect in swollen elastomers - Loo, M.S.; Andriyana, A.; Lee, S.L.; Tan, N.H. (Maney Publishing, 2014)
Owing to its special traits, rubber has been used extensively for over decades in damping, automotive and sealing applications. In certain applications, rubber is not only subjected to fluctuating loading but also exposure to aggressive liquids. Under cyclic loading conditions, both dry and swollen rubber exhibit strong inelastic responses portrayed by the stress softening owing to Mullins effect. These inelastic responses are believed to affect the durability analysis and hence, it becomes an essential consideration when performing the analysis. In this study, a simple phenomenological approach is developed by extending the concept of pseudo-elastic model. In order to investigate the effect of swelling on the stress softening owing to Mullins effect, the swollen rubbers are obtained by immersing them in biodiesel at room temperature for two different immersion durations: 1 and 2 weeks. The resulting inelastic response, particularly stress softening, is investigated. The experimental data obtained are then treated to implement the concept of pseudo-elastic in modelling the stress-strain response of both dry and swollen rubber. Results show that the proposed model agrees qualitatively well with the experimental observations.